The Question of Fraudulent Registration of Ships and Fraudulent Ship Registries; the Response of the International Community - Daniil, Georgios; Saviolakis, Panagiotis (Transactions on Maritime Science, 2024)
The aim of this paper is to address the issue of fraudulent registration and fraudulent Ship Registries, mainly as a means of concealing illicit activities, such as piracy, slavery, maritime migration, IUU fishing, and the evasion of UN sanctions. The method that has been followed includes the presentation of all types of fraudulent flagging as reported by the interested Flag States, Port States, and the associated international organisations of IMO and FAO. The analysis compares the findings that have been collected by the various sources and the drawing of strong conclusions. The results of this essay extend to cover the various forms of fraudulent registration, the legal framework that governs the registration of ships, and the proposed measures to deal with this phenomenon. The novelty lies in the multi-level approach of fraudulent registration, covering all of its forms, and the solutions proposed, either already applied or innovative. In conclusion, insufficiency to deal with this phenomenon so far leaves room for the application of new strategies, like the ones proposed in the current essay.